Effect of acute lipopolysaccharide-induced inflammation in intracerebroventricular-streptozotocin injected rats. (February 2016) - Murtishaw, Andrew S.; Heaney, Chelcie F.; Bolton, Monica M.; Sabbagh, Jonathan J.; Langhardt, Michael A.; Kinney, Jefferson W.
Abstract: Lipopolysaccharide (LPS) is often used to investigate the exacerbatory effects of an immune-related challenge in transgenic models of various neurodegenerative diseases. However, the effects of this inflammatory challenge in an insulin resistant brain state, as seen in diabetes mellitus, a major risk factor for both vascular dementia (VaD) and Alzheimer's disease (AD), is not as well characterized. We investigated the effects of an LPS-induced inflammatory challenge on behavioral and biological parameters following intracerebroventricular (ICV) injection of streptozotocin (STZ) in male Sprague–Dawley rats. Subjects received a one-time bilateral ICV infusion of STZ (25 mg/mL, 8 μL per ventricle) or ACSF. One week following ICV infusions, LPS (1 mg/mL, i.p.) or saline was administered to activate the immune system. Behavioral testing began on the 22nd day following STZ-ICV infusion, utilizing the open field and Morris water maze (MWM) tasks. Proteins related to immune function, learning and memory, synaptic plasticity, and key histopathological markers observed in VaD and AD were evaluated. The addition of an LPS-induced immune challenge partially attenuated spatial learning and memory deficits in the MWM in STZ-ICV injected animals. Additionally, LPS administration to STZ-treated animals partially mitigated alterations observed in several protein levels in STZ-ICV alone, including NR2A, GABAB1, and β-amyloid oligomers. These results suggest that an acute LPS-inflammatory response has a modest protective effect against some of the spatial learning and memory deficits and protein alterations associated with STZ-ICV induction of an insulin resistant brain state. Highlights: An inflammatory challenge was administered in STZ-ICV animals. STZ impaired spatial memory (MWM) and altered brain protein expression. The addition of LPS (STZ/LPS) conferred a modest protection in the MWM. STZ/LPS prevented alterations in several brain proteins. Acute inflammation may play beneficial role in preventing early AD-like symptoms.